Suicide by gender and 10-year age groups during the COVID-19 pandemic vs previous five years in Japan: An analysis of national vital statistics. (November 2021) - Eguchi, Akifumi; Nomura, Shuhei; Gilmour, Stuart; Harada, Nahoko; Sakamoto, Haruka; Ueda, Peter; Yoneoka, Daisuke; Tanoue, Yuta; Kawashima, Takayuki; Hayashi, Takehiko I.; Arima, Yuzo; Suzuki, Motoi; et al.
Highlights: Studies have raised concerns that COVID-19 has exacerbated multiple factors that may increase suicides. We provide detailed estimates of the additional suicide burden during the COVID-19 pandemic in Japan by gender, using for the first time daily vital statistics data from the Ministry of Health, Labour and Welfare from January through November 2020. This study found that compared with previous years, suicide cases in 2020 in Japan have increased from late July to November for women in all age groups and for men in the 20–29 and 80+ age group. Targeted interventions based on age and gender, and outreach strategies adapted to the conditions of lockdown, may be more effective in reducing suicide during the COVID-19 pandemic in Japan. Abstract: Using daily vital statistics data from the Japanese Ministry of Health, Labour and Welfare, we provide the first weekly and age-group-specific estimates of the additional suicide burden during the COVID-19 pandemic in Japan by gender, from January through November 2020. Our results indicate that compared with the previous five years, suicide cases in 2020 in Japan have increased from late July to November for women in all age groups and for men in the 20–29 and 80+ years age group. Targeted interventions based on age and gender might be more effective in reducing suicide during the COVID-19 pandemic in Japan.